Effective bond length and bond behaviour of FRP externally bonded to timber. (1st October 2017) - Vahedian, Abbas; Shrestha, Rijun; Crews, Keith
Highlights: A new model for effective bond length for FRP-to-timber joints has been developed. High agreement between measured and predicted effective bond length has been achieved. A modified single shear test setup has been successfully developed. Abstract: Despite a large number of studies on estimating the effective bond length from the characteristics of the component materials, key parameters governing the effective bond length for FRP-to-timber joint have not been suggested by any of the current Codes and developed theories to date mostly cover FRP-to-concrete joints. Also, most theoretical bond strength models have been derived based on effective bond length. Therefore, to achieve a satisfactory bonded joint, the effectiveness of bond length is required to be accurately considered. This research study investigates 136 FRP-to-timber joints subjected to pull-out tests in order to determine the stress and strain distribution profiles along the interface and subsequently analyses the results to undertake direct measurement of the effective bond length. In addition, a modified test set up has been developed and is presented. A novel theoretical model has been established through regression analysis of bond length data and accordingly a new predictive model for effective bond length for FRP-to-timber joints has been developed. A comparative analysis between the results of the experimental pull-out tests results and those predicted from the analytical model indicates a satisfactory correlation is achieved between measured and predicted effective bond length, verifying the validity of the new model.